Poor glycemic control and smoking and drinking history rather than bacterial virulence contribute to the development of invasive Klebsiella pneumoniae liver abscess: a case–control study in Northeast China - Chen, Jingjing; Wang, Xinyi; Wang, Qihui; Tian, Sufei; Li, Fushun; Wang, Ruixuan; Chang, Zhihui; Chu, Yunzhuo (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to investigate the clinical and microbiological characteristics of invasive and noninvasive Klebsiella pneumoniae liver abscesses (KPLAs) and elucidate the risk factors for invasive KPLA.MethodsWe conducted a case–control study involving 50 patients with invasive KPLA and 50 patients with noninvasive KPLA from two medical centers between 2019 and 2024. Demographic and clinical data were collected for all patients from the hospital medical records system. Univariate and multivariate analyses were then performed to compare the characteristics of invasive and noninvasive KPLAs. In addition, antimicrobial resistance testing and whole-genome sequencing were performed for 50 K. pneumoniae strains from one medical center.ResultsThe comparison of patients with invasive and noninvasive KPLAs revealed that diabetes mellitus, smoking history, drinking history, smaller maximum diameter of abscess, neutrophil count, fasting blood glucose, blood urea nitrogen, and length of hospital stay were independent risk factors for invasive KPLA. Phylogenetic analysis revealed that K. pneumoniae strains from patients with invasive and noninvasive KPLAs were intermingled. ST23 with K1 serotype was the predominant sequence type (66.0%), followed by ST65 with K2 serotype. Multilocus sequence types, capsular serotypes, antimicrobial resistance patterns, virulence genes, and SNPs of K. pneumoniae strains isolated from patients with invasive and noninvasive KPLAs showed no significant differences between the two patient groups.ConclusionOverall, our results indicate that patients’ contaminant conditions, such as poor glycemic control, smoking history, and drinking history, rather than bacterial virulence, contribute to the development of invasive KPLA.